Perceptions and readiness to use telerehabilitation service during the COVID‑19 pandemic among physiotherapists: a review / Rabiatul Adawiah Abdul Rahman and Nurul Husna Mohd Nasir - Abdul Rahman, Rabiatul Adawiah; Mohd Nasir, Nurul Husna (UiTM Press, 2023)
This paper reviewed the perceptions and readiness to use telerehabilitation service during the COVID-19 pandemic among physiotherapists. A comprehensive overview on acceptance and insights of telerehabilitation will result in the successful implementation of the system. A review of the literature from 2019 to 2022 was performed using MEDLINE, Scopus, ScienceDirect and Google Scholar database. The authors explored all systematic findings to ensure inclusion criteria were met. Ten studies were appraised, and 7 selected studies were reviewed. Most of the findings showed positive perceptions towards telerehabilitation and willingness to use this technology-based service. Inadequate training, lack of connections between information and communication technology (ICT) experts and clinicians, patient privacy and confidentiality, patient ability to use ICT, and internet connection issues are some of the reported barriers that may prevent physiotherapists from using telerehabilitation.